2007
DOI: 10.1007/s10895-007-0220-2
|View full text |Cite
|
Sign up to set email alerts
|

Transport of a Cancer Chemopreventive Polyphenol, Resveratrol: Interaction with Serum Albumin and Hemoglobin

Abstract: Resveratrol is a natural phytoalexin with pharmacologic effects on several human diseases: carcinogenesis, coronary heart disease and neurodegenerative disease. Due to its poor water solubility, resveratrol must be bound to proteins to keep it at a high concentration in serum. In our work, the bindings of resveratrol to plasma proteins, human serum albumin (HSA) and hemoglobin (Hb), have been investigated systematically by fluorescence quenching technique, synchronous fluorescence, UV-vis absorption spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 24 publications
8
64
1
1
Order By: Relevance
“…First results obtained by N'soukpoe-Kossi et al indicated a partial stabilization of protein secondary structure at high RSV content and show no major alterations at low RSV concentrations (0.125 mM), whereas at high pigment content (1 mM), major increases of a-helices from 57% (free HSA) to 62% and a decrease of b-sheets from 10% (free HSA) to 7% occurred in the RSV-HSA complexes [58]. On the contrary, Lu et al show, as similar to the results obtained with BSA, a decrease in the a-helical structure of HSA (2 mM) with a range of RSV concentration (0.8-3.2 mM) [57]. In this study, it seems that HSA has only one binding site for RSV as similar to haemoglobin (Hb) [57].…”
Section: Albuminsupporting
confidence: 59%
See 1 more Smart Citation
“…First results obtained by N'soukpoe-Kossi et al indicated a partial stabilization of protein secondary structure at high RSV content and show no major alterations at low RSV concentrations (0.125 mM), whereas at high pigment content (1 mM), major increases of a-helices from 57% (free HSA) to 62% and a decrease of b-sheets from 10% (free HSA) to 7% occurred in the RSV-HSA complexes [58]. On the contrary, Lu et al show, as similar to the results obtained with BSA, a decrease in the a-helical structure of HSA (2 mM) with a range of RSV concentration (0.8-3.2 mM) [57]. In this study, it seems that HSA has only one binding site for RSV as similar to haemoglobin (Hb) [57].…”
Section: Albuminsupporting
confidence: 59%
“…The affinity and the binding of RSV with BSA suggest that the polyphenol binds to HSA, the major plasma protein in humans [56]. Indeed, HSA is able to bind RSV and to maintain a high concentration in human serum [57]. First results obtained by N'soukpoe-Kossi et al indicated a partial stabilization of protein secondary structure at high RSV content and show no major alterations at low RSV concentrations (0.125 mM), whereas at high pigment content (1 mM), major increases of a-helices from 57% (free HSA) to 62% and a decrease of b-sheets from 10% (free HSA) to 7% occurred in the RSV-HSA complexes [58].…”
Section: Albuminmentioning
confidence: 99%
“…It is the principal agent responsible for the osmotic pressure of blood, for transport of fatty acids, and for the sequestration and transportation of bilirubin . Other less well-defined functions included transport of tryptophan, cysteine, and various hormones and it is a source of amino acids for peripheral tissues (Lu et al, 2007). It is synthesized almost exclusively by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…RSV has poor water solubility and thus has to be bound to plasma proteins to assure its body distribution and bioavailability [66]. Indeed, in its transport, RSV can bind to serum proteins [67] such as lipoproteins, hemoglobin, and albumin which facilitate its carrier mediated cellular uptake and then it can passively diffuse through the plasma membrane [68,69] investigated the binding properties of RSV to plasma proteins, such as human serum albumin (HSA) and hemoglobin (Hb) and confirmed that both complexes formed are spontaneous and exothermic. The binding constant of RSV-HSA complex is larger than that of RSV-Hb, which indicates the higher affinity of HSA to RSV.…”
Section: Distributionmentioning
confidence: 99%
“…Hydrophobic interactions seem to play a major role in the binding of RSV to the hydrophobic cavity of HSA, and hydrogen bonding is the main force involved in the binding of RSV to the central cavity of Hb where some residues interact directly with the hydroxyl groups of the compound. Electrostatic interactions can also be involved in the formation of both complexes since residues with positive charge are in the proximity of the binding compound [69].…”
Section: Distributionmentioning
confidence: 99%